Adolescent Knowledge About the Dangers of Free Sex - Fitriani Fitriani; Ridni Husnah; Ichi Salsabila (UIMA Press, 2021)
Background: Counseling is a way of spreading messages about reproductive health in this case sex education which is an important message about the dangers of sex. Objectives: The purpose of this study was to determine the effect of counseling on the dangers of free sex on the knowledge of adolescents in Mts Darul Falah Batam District in 2021. Methods: The research method is a quantitative study using the Quasy Experiment method with a